2016
DOI: 10.5941/myco.2016.44.4.237
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Marine-DerivedAspergillusfrom Tidal Mudflats and Sea Sand in Korea

Abstract: Aspergillus (Trichocomaceae, Eurotiales, and Ascomycota) is a genus of well-defined asexual spore-forming fungi that produce valuable compounds such as secondary metabolites and enzymes; however, some species are also responsible for diseases in plants and animals, including humans. To date, 26 Aspergillus species have been reported in Korea, with most species located in terrestrial environments. In our study, Aspergillus species were isolated from mudflats and sea sand along the western and southern coasts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 66 publications
2
19
0
Order By: Relevance
“…These were isolated from different sources including meju [48], chronic granulomatous patient [61], poultry farming soil [62], tidal mudflats, and sea sand [17]. In this study, A. tennesseensis was isolated from sea water and dead moths.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These were isolated from different sources including meju [48], chronic granulomatous patient [61], poultry farming soil [62], tidal mudflats, and sea sand [17]. In this study, A. tennesseensis was isolated from sea water and dead moths.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, a new Aspergillus species, A. koreanus, has been described [16]. Six more species were recorded recently from Korea, A. allahabadii and A. caninus from soil, A. sojae from meju, and A. montenegroi, A. rhizopodus, and A. tabacinus from tidal mudflats and sea sand [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we sought to determine whether the glucose-dependent activation of PykA in V. vulnificus has anything to do with the glucose-dependent H 2 O 2 production by its fungal neighbors. Because the V. vulnificus CMCP6 strain was originally isolated from a patient in the west coast of Korea ( Kim et al, 2003 ), we tested the GOX activity from the two fungal strains belonging to the Aspergillus genus isolated from the west coast of Korea ( Lee et al, 2016 ) ( Figure 4A ). Both zymographic analyses ( Figure 4B ) and coupled enzyme assays with peroxidase and o -dianisidine ( Figure 4C ) revealed that A. welwitschiae produced a significant amount of GOX when grown in the presence of glucose, whereas little GOX was detected in the crude extract of A. fumigatus cells.…”
Section: Resultsmentioning
confidence: 99%
“…Harwood took the lead on reviewing and editing the final draft assisted by Michael J. Sadowsky, Julie L. Kinzelman and Warish Ahmed. (Lee et al 2016, Sabino et al 2014 Fungi Candida albicans Candidosis (systemic and localized) Not available (Loureiro et al 2005, Vogel et al 2007, WHO 2003 CFU: colony forming unit; PFU: plaque forming unit. Eichmiller, J.J., Borchert, A.J., Sadowsky, M.J. and Hicks, R.E.…”
Section: Author Contributionsmentioning
confidence: 99%